Early childhood diets on the Nile: δ13C and δ15N in serial samples of permanent first molars in an elite Meroitic population from Sai Island, Sudan. (19th June 2018) - Eerkens, Jelmer W.; de Voogt, Alex; Dupras, Tosha L.; Francigny, Vincent; Greenwald, Alexandra M.
Abstract: We explore early childhood dietary patterns in a Late Meroitic (first–fourth century CE) population ( N  = 11) from Sai Island, Sudan, using stable carbon and nitrogen isotopes in serial samples from permanent first molar dentin. Results suggest an average age of weaning of 2.7 years, but with significant interindividual variation in the timing of weaning, with evidence for a later age at weaning for two females (average 3.5 years) compared with four males (average 2.3 years). Isotopic results support significant input of C4 plant‐derived protein in the weanling and postweaning diets (20–50%), perhaps in the form of plant‐rich gruels, but no significant difference in the composition of diet by sex. We observe the highest interindividual variation in diets immediately postweaning (ca. 4–5 years), with increasing homogeneity in diet thereafter. Together, the results provide new insight into the early dietary histories of the elite Meroites along this part of the Nile.